Human papillomavirus infection and esophageal cancer: a case report - Miguel A. Serra Valdés; Andrés W. Fojo Mallo; Nordal González Valera; Maritza Cardosa Samón; Marcelina García Tassé; Yordanka Y. Aleaga Hernández (Medwave, 2012)
Introduction. Currently over 216 types of human papillomavirus (HPV) have been reported, but only 100 have been fully sequenced. They are able to infect cells of the basal layer of any epithelium. Evidence of HPV oncogenicity has been found. Objective. To describe a case of esophageal HPV infection associated to cancer of the esophagus. Case report. 63 years-old, African and rural origin, single, female housewife with the habit of smoking and frequent ingestion of alcohol. Four months before the diagnosis was established, the patient began to gradually develop dysphagia to solids and weight loss. Upper endoscopy shows a proliferative ulcerated lesion in the middle third of the esophagus. Biopsy is consistent with esophageal squamous cell carcinoma. Cytology is suggestive of papillomavirus infection. Discussion. Prior esophageal papillomatosis and other risk factors contributed to the occurrence of esophageal carcinoma. Histopathology was consistent with the diagnosis of squamous cell carcinoma probably caused by HPV infection. Conclusion. The association between papilloma virus and esophageal cancer is rare but can be diagnosed if it is suspected and other risk factors are present, as well as if there is access to modern diagnostic means.